Perencanaan Keuangan untuk Bisnis dengan Teknologi: Adaptasi Strategis di Era Digital - Zulfikar Yahya Anhar; Dana Bahari Sitepu; Muhammad Zacky; Fajar Rhenzy Elaza; Deby Aryo Saputro (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
In an increasingly complex and dynamic business environment, financial planning has become a crucial element to ensure business continuity and sustainability. Amidst the rapid development of digital technology, the financial planning process has undergone a significant transformation from a manual system to a technology-based approach. This article examines how the integration of technologies such as accounting software, fintech, artificial intelligence (AI), and big data is changing the landscape of business financial planning. Using a descriptive qualitative approach and literature study, this study shows that the use of technology not only improves operational efficiency but also strengthens prediction accuracy, data transparency, and decision-making accuracy. However, challenges such as limited financial literacy, implementation costs, and data security risks remain obstacles that need to be overcome. This study recommends adaptive and collaborative strategies to drive digital transformation in sustainable financial planning.